Eye care compliance in intensive care units: A concept analysis - Abdulkareem S. Iblasi; Cansu Polat Dünya; Zoelfikar Dafalla Mohamed; I Gede Juanamasta (Belitung Nursing Journal, 2026)
Background: Despite the availability of evidence-based eye-care protocols, compliance among nurses in intensive care units (ICUs) remains inconsistent. Conceptual ambiguity between adherence, compliance, and protocol implementation has limited the development of valid measures and targeted interventions. Objective: To clarify and define the concept of Eye Care Compliance in ICUs through a systematic concept analysis. Methods: This concept analysis followed the eight-step framework of Walker and Avant. CINAHL Plus, PubMed, Scopus, Web of Science, and ScienceDirect were searched for studies published between 2015 and 2025. Database-specific search strings and eligibility criteria were applied, and studies were screened and selected based on predefined inclusion and exclusion criteria. Results: Of 653 records identified, 19 studies met the inclusion criteria. Eye Care Compliance was clarified as an observable nursing behavior (what nurses do), distinct from protocol compliance (following externally imposed instructions) and protocol implementation (organizational adoption of a guideline). Three defining attributes were identified: (1) consistent care: reliable, repeated delivery of all protocol-specified procedures for all at-risk patients; (2) timely care: alignment of eye-care activities with evidence-based frequency recommendations and the patient’s evolving risk profile; and (3) documented care: systematic recording of assessments, interventions, and their timing to ensure continuity and auditability. Conclusions: Eye Care Compliance is a distinct, nurse-mediated behavioral construct referring to the observable enactment of structured, evidence-based ocular protection in the ICU. This concept is operationalized as the behavior pattern in which ICU nurses systematically perform and record all protocol-specified ocular protection procedures—assessment, cleansing, eyelid closure or protection, and lubrication—for every patient meeting defined risk criterion, at the intervals required by evidence-based guidelines, with each episode documented to ensure care continuity and accountability.